Open-tubular radially cyclical electric field-flow fractionation (OTR-CyElFFF): an online concentric distribution strategy for simultaneous separation of microparticles. Issue 19 (27th August 2020) - Liu, Lu; Yang, Cui; Liu, Cuicui; Piao, Jishou; Kaw, Han Yeong; Cui, Jiaxuan; Shang, Haibo; Ri, Hyok Chol; Kim, Ji man; Jin, Mingshi; Li, Donghao
Abstract : An open-tubular radially cyclical electric field-flow fractionation technique which realizes the online separation of microparticles in a functional annular channel is proposed in this study. Abstract : An open-tubular radially cyclical electric field-flow fractionation technique which achieves the online separation of microparticles in a functional annular channel is proposed in this study. The system was set up by using a stainless steel tube and a platinum wire modified with ionic liquid/mesoporous silica materials as the external and internal electrodes. The feasibility for online separation of various particles was experimentally demonstrated. Particles in the channel were affected by a radial electric field and field-flow fractionation (FFF). On the cross section, different particles showed distinctive migration distances depending on their own properties and the different magnitudes of forces being exerted. The same kind of particles form an annular distribution within the same annulus while different particles form annular distributions at varied concentric annuli through electrophoresis. Under a laminar flow of FFF, different sizes of particles formed a conical arrangement within the annular separation channel. With the joint influence of electric field and flow field, different trajectories were obtained and the particles were eventually separated. Voltage, frequency and duty cycle value are the main parameters affecting the separation of particles. By adjusting these parameters, particles migrate in a zigzag trajectory on one side of the electrodes (mode I) and reach both sides of the electrodes (mode II). Six polystyrene particles were completely separated with high resolution within several minutes. Our system offers numerous advantages of label-free, high-resolution and online separation without tedious operations, and it is a promising tool for the effective separation of various micro-objects.